2016
DOI: 10.1186/s12889-016-3354-9
|View full text |Cite
|
Sign up to set email alerts
|

“Did you ever drink more?” A detailed description of pregnant women’s drinking patterns

Abstract: BackgroundThis paper presents drinking patterns in a prospective study of a population-based cohort of 1570 pregnant women using a combination of dose and timing to give best estimates of prenatal alcohol exposure (PAE). Novel assessments include women’s special occasion drinking and alcohol use prior to pregnancy recognition.MethodsInformation on up to nine types of alcoholic drink, with separate frequencies and volumes, including drinking on special occasions outside a ‘usual’ pattern, was collected for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
151
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 106 publications
(155 citation statements)
references
References 38 publications
3
151
1
Order By: Relevance
“…A more recent study from Australia of 1570 participants showed that these rates have risen to 39% (Muggli et al, 2016). This same study also analysed the period prior to pregnancy recognition, in which 12% of women admitted to binge drinking regularly, with an additional 6% admitting to binge drinking on one occasion (Muggli et al, 2016). In total over the periconception period, 27% of women drank alcohol, with 87% ceasing alcohol consumption after pregnancy recognition (Muggli et al, 2016).…”
Section: Prevalence Of Maternal Alcohol Consumptionmentioning
confidence: 98%
See 4 more Smart Citations
“…A more recent study from Australia of 1570 participants showed that these rates have risen to 39% (Muggli et al, 2016). This same study also analysed the period prior to pregnancy recognition, in which 12% of women admitted to binge drinking regularly, with an additional 6% admitting to binge drinking on one occasion (Muggli et al, 2016). In total over the periconception period, 27% of women drank alcohol, with 87% ceasing alcohol consumption after pregnancy recognition (Muggli et al, 2016).…”
Section: Prevalence Of Maternal Alcohol Consumptionmentioning
confidence: 98%
“…A population study from Australia showed that approximately 14% of women drank more than 5 standard drinks in 1 day of the 3 months prior to pregnancy (Colvin et al, 2007). A more recent study from Australia of 1570 participants showed that these rates have risen to 39% (Muggli et al, 2016). This same study also analysed the period prior to pregnancy recognition, in which 12% of women admitted to binge drinking regularly, with an additional 6% admitting to binge drinking on one occasion (Muggli et al, 2016).…”
Section: Prevalence Of Maternal Alcohol Consumptionmentioning
confidence: 99%
See 3 more Smart Citations